A Grounded Theory on School Nursing Experiences With Major Pandemic Diseases - Youn-Joo Um PhD, RN; Yun-Jung Choi PhD, RN, PMHNP (SAGE Publishing, 2022)
This study was conducted to develop a substantive theory on school nurses' experiences responding to infectious diseases by applying the grounded theory method to explore their experiences and derive related concepts. Study participants were 20 school nurses with experiences coping with infectious diseases while working in schools. The research question of this study was "What kind of experience did the school nurses have in response to infectious diseases?" The analysis included open, axis, and selective coding. We derived 164 concepts, 45 subcategories, and 17 categories. Further, paradigm, situation, and school infectious disease response control tower models were derived. The results of this study can serve as bottom-up policy data to understand the current situation surrounding school infectious disease management through the experiences of school nurses.